Congenital H-type recto-vaginal fistula with normal anus: a case report - Samuel Kefiyalew Kelbessa; Berhanu Nigusse Bikila; Amanuel Mesfin Oljira (Journal of Pediatric Surgery Case Reports)
Introduction: Congenital H-type fistula is a rare anomaly characterized by a recto-urogenital connection, with the external anal opening potentially positioned normally or ectopically. This type of fistula represents only 0.1 % of all anorectal malformations in Africa. Case description: A 6-week-old female infant was referred to our clinic after feces were noted coming from both the anus and the vaginal vestibulum. Examination under anesthesia revealed a non-stenotic anus and a fistulous opening on the anterior rectal wall, 1.5 cm above the dentate line. Preoperative VACTERL screening was normal. The infant received two doses of a cleansing enema and intravenous preoperative antibiotics (ceftriaxone and metronidazole). Under general anesthesia, a loop proximal sigmoid colostomy was performed. The infant was positioned prone for a transanal anterior rectal pull-through. A Swenson-like dissection was conducted on the anterior rectal wall for 4 cm, leaving the posterior wall intact. The vaginal opening was repaired using interrupted sutures. The left ischiorectal fat pad was harvested and placed between the repaired vaginal wall and the anterior rectal wall. The full-thickness rectal wall was then pulled over and anastomosed to the anus. The patient was discharged home after three days. The colostomy was closed three months later. One year after the operation she has no signs of fistula recurrence. Conclusion: A transanal anterior rectal pull-through with protective colostomy seems to be an effective option for the management of H-type congenital rectovaginal fistulas in neonates and infants.